(untitled) (Fiep Bulletin - online, 2020)
The importance of applying pedagogical tact with their respective derivatives to identify, encourage and use moral and universal values, which allow the teaching practice in physical education with responsibility and co-responsibility, when carrying out a multidisciplinary work, in which we involve the physical education teacher -group-student-parents-managers and administrative teachers who lead our students, to have positive behaviors that allow them to have a better coexistence in school, at home and interact freely and autonomously through the sessions of physical education.